FREQUENCY OF HYPERTRIGLYCERIDEMIA IN TYPE 2 DIABETIC PATIENTS RECEIVING STATIN THERAPY AND ITS CORRELATION WITH GLYCEMIC CONTROL - Ullah, Zafran; Malik, Suleman Elahi; Ghaffar, Tahir; Kanwal, Shaista; Noor, Aqil; Aamir, Azizul Hassan (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the frequency of hypertriglyceridemia in type 2 diabetic patients who are on statin therapy and its correlation with glycemic control. Methodology: This cross sectional study was conducted from December 2019 to July 2020 in the outpatient department of Endocrinology unit, Hayatabad medical complex Peshawar. A total of 99 diabetic patients, who were regularly taking statins for hypertriglyceridemia, were included using non probability consecutive sampling technique. All eligible patients were assessed for hypertriglyceridemia and glycemic status. Data was analyzed with SPSS version 23. Results were presented as tables and bar charts. Results: The mean age of patients was 53.2 (SD ± 10.1) years. Males were 54%. The mean duration of diabetes was 5.8 (SD ± 2.1) years, with 59.6% of the patients having duration of diabetes of more than 5-years. The mean BMI of samples was 26.7 (SD= ±3.0) kg/m2, among them 63.6% had BMI of more than or equal to 23 kg/m2. The mean value of HbA1c of samples was 8.1% (SD ± .05), among them 55.6% had an HbA1c ranged from 8.1 – 9.0 %. The frequency of hypertriglyceridemia was 35.4%. Glycated haemoglobin (HbA1C) level had a statistically significant positive correlation with hypertriglyceridemia. Body mass index (BMI) and duration of diabetes also correlated positively with hypertriglyceridemia, although the correlation wasn't significant. Conclusion: A significant percentage of type 2 diabetic patients rceiving statin therapy have hypertriglyceridemia, with glycemic control having a significant impact on triglycerides level.